(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research aims to study the effectiveness of the communication activities carried out by the Recall Center in raising consumer awareness of defective products and to determine the extent of their impact on consumer response to these campaigns. The research also seeks to identify the most commonly used communication methods for disseminating recall information, in addition to analyzing the factors that influence consumer engagement with these campaigns. The research relied on a descriptive analytical approach, where data was collected from a sample of 400 consumers using an electronic questionnaire. The data were statistically analyzed to test the hypotheses. The results showed that social media was the primary source of information about recalls (52.5%), followed by official websites (41.3%) and television (36.3%). The results also indicated a statistically significant relationship between the type of communication methods used and the extent of dissemination of recall information, with a correlation coefficient of 0.084 at a significance level of 0.039. On the other hand, the study revealed that consumer awareness plays a major role in their response to recall campaigns, with 43.8% of participants reporting that communication activities significantly impact their purchasing decisions. It also revealed that 65% of consumers took action after receiving information about a product recall, indicating the effectiveness of these campaigns in changing consumer behavior. The study recommended improving the quality of communication activities by simplifying information and increasing engagement with consumers via digital media, in addition to enhancing credibility and transparency by providing periodic reports on recalls and their impact. It also emphasized the importance of employing modern technologies such as artificial intelligence and smart notifications to ensure that information reaches consumers quickly and effectively.